Impact of stress in ICP‐CVD SiNx passivation films on the leakage current in AlGaN/GaN HEMTs. Issue 15 (1st July 2018) - Cho, S.‐J.; Li, X.; Guiney, I.; Floros, K.; Hemakumara, D.; Wallis, D.J.; Humphreys, C.; Thayne, I.G.
Abstract : The impact of the stress in room temperature inductively coupled plasma chemical vapour deposited (ICP‐CVD) SiN x surface passivation layers on off‐state drain ( I DS‐off ) and gate leakage currents ( I GS ) in AlGaN/GaN high electron mobility transistors (HEMTs) is reported. I DS‐off and I GS in 2 μm gate length devices were reduced by up to four orders of magnitude to ∼10 pA/mm using a compressively stressed bilayer SiN x passivation scheme. In addition, I on / I off of ∼10 11 and subthreshold slope of 68 mV/dec were obtained using this strain engineered surface passivation approach.